Poligami Dalam Islam: Tinjauan Hadis Berdasarkan Teori Dasar Ilmu Hadis - Yulanda Yulanda; Valentina Ramadhany (CV. ITTC INDONESIA, 2025)
Polygamy is a permissible practice in Islam, provided that justice is the primary condition, as stated in Surah An-Nisa, verse 3. However, this verse does not specify the form of justice intended, thus opening up room for diverse interpretations among Muslims. In this context, the hadith of the Prophet Muhammad (peace be upon him) serves as an authoritative reference in explaining, limiting, and implementing the law of polygamy more concretely. This study aims to examine the relationship between the basic theory of hadith science, which includes its definition, classification, status, function, and the law of denying hadith, and the understanding of polygamy in Islam. This research uses a qualitative method with a library research approach. The results of the study indicate that the hadith discussing polygamy are mostly authentic and have binding legal force. Through the theory of hadith science, it can be understood that hadith is not only a complement to the Qur'an, but also a source of law that has an explanatory, limiting, and controlling function regarding the practice of polygamy. Thus, understanding the law of polygamy cannot be separated from the methodology of authentic hadith science.